Suburbanization: A Post World War II Phenomenon in the Athens Metropolitan Area, Greece - Kostas Rontos; Christos Mavroudis; Theodore Georgiadis (European Regional Science Association (ERSA), 2006)
This article studies the phases of urban development in Athens, the biggest metropolitan center of the country, in combination with the development of the Greek economy during the post world war II era, by applying techniques suggested by the theory of spatial cycle. Before application, an extended reference to the theoretical background will be presented, so that a comprehensive view of the spatial cycle hypothesis is established. Á short historical analysis of the Greek economy will also be provided, so that the impact of several historical factors on the recent evolution of Athens Metropolitan Area be better understood. Since the beginning of the post-war period, the Athens Metropolitan Area has been going through a certain phase, i.e. the phase of suburbanization. Recently (1981-2001) the afore-mentioned area has shifted from the first stage of this phase to the second, i.e. from relative to absolute decentralization, facing not only a complete loss of core city population but also memorisation, unemployment and other depressive phenomena. As differences among western, southern or northern suburbs appear, an intra-suburb analysis will be carried out in order to identify the direction of urban evolution through time. The recent decline in the development of suburbs, in juxtaposition with the rapid emergence of some independent urban areas outside the Athens Metropolitan Area, provides some evidence of potential movement towards the next phase of disurbanization in the near future.
Keywords: 330